Technical strategy of triple jump: Differences of inverted pendulum model between hop-dominated and balance techniques - Fujibayashi, N.; Otsuka, M.; Yoshioka, S.; Isaka, T. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: The present study aims to cross-sectionally clarify the characteristics of the motions of an inverted pendulum model, a stance leg, a swing leg and arms in different triple-jumping techniques to understand whether or not hop displacement is relatively longer rather than step and jump displacements. METHODS: Eighteen male athletes performed the triple jump with a full run-up. Based on the technique of the jumpers, they were classified as hop-dominated (N.=10) or balance (N.=8) jumpers. The kinematic data were calculated using motion capture and compared between the two techniques using the inverted pendulum model. RESULTS: The hop-dominated jumpers had a significantly longer hop displacement and faster vertical center-of-mass (COM) velocity of their whole body at hop take-off, which was generated by faster rotation behaviors of inverted pendulum model and faster swinging behaviors of arms. Conversely, balance jumpers had a significantly longer jump displacement and faster horizontal COM velocity of their whole body at take-off, which was generated by a stiffer inverted pendulum model and stance leg. CONCLUSIONS: The results demonstrate that hop-dominated and balance jumpers enhanced each dominated-jump displacement using different swing- and stance-leg motions. This information may help to enhance the actual displacement of triple jumpers using different jumping techniques.